Evaluation of Trichoderma spp. for the control of seedling rot disease of cardamom (Elettaria cardamomum Maton) - THOMAS, R SUSEELA BHAI, JOSEPH (Journal of Spices and Aromatic Crops, 1998)
Trichoderma viride and T. harzianum were evaluated as seed dressing prior to sowing of seeds and as soil application in nursery beds at the time of transplanting cardamom (Elettaria cardamomum) seedlings for the control of seedling rot or damping off caused by Pythium vexans. Coating of seeds with Trichoderma spp. did not alter the percentage of germination but reduced the percentage of damping off in sick soil. Soil drenching of Trichoderma spp. mascerates 1 week prior to transplanting of seedlings in sick soils was effective in reducing seedling mortality compared to Trichoderma application after transplanting or as seedling dip.